Animosity based on traditional enmity versus other causes. Issue 3 (25th June 2021) - Campo, Sara; Alvarez, Maria D.
Abstract : Purpose: The study aims to investigate the concept of animosity that is based on traditional enmity and that which originates from other grounds. The study examines whether animosity that is based on these different causes has differing effects on perceptions and purchase decisions of the tourist destination product. Design/methodology/approach: The study is based on data collected via an online questionnaire concerning the perceptions, feelings and visitation intentions of Chinese individuals toward Japan, as the traditional enemy, or toward other countries without a history of enmity with China. A model of relationships is tested. Findings: The findings determine that animosity is formed differently depending on the target country. In addition, the influence of animosity on intention to visit and perceived risk of visiting the destination vary when animosity is based on traditional enmity reasons and when it is grounded on other causes. The influence of animosity on risk perceptions is also verified. Practical implications: The study provides information that can be used to manage a country's brand in the Chinese market and to segment Chinese consumers based on their feelings of animosity toward certain countries. Originality/value: The study is original as it compares animosity and its influence when it is based on causes related to traditional enmity and when it is grounded on other reasons. It is also one of the few studies to address the relationship between animosity and perceived risk.